Dietary Cholesterol, Serum Lipids, and Heart Disease: Are Eggs Working for or Against You? - Blesso, Christopher N. (Nutrients, 2018)
The relationship between blood cholesterol and heart disease is well-established, with the lowering of serum low-density lipoprotein (LDL)-cholesterol being the primary target of preventive therapy. Furthermore, epidemiological studies report lower risk for heart disease with higher concentrations of high-density lipoprotein (HDL)-cholesterol. There has also been considerable interest in studying the relationship between dietary cholesterol intake and heart disease risk. Eggs are one of the richest sources of cholesterol in the diet. However, large-scale epidemiological studies have found only tenuous associations between the intake of eggs and cardiovascular disease risk. Well-controlled, clinical studies show the impact of dietary cholesterol challenges via egg intake on serum lipids is highly variable, with the majority of individuals (~2/3 of the population) having only minimal responses, while those with a significant response increase both LDL and HDL-cholesterol, typically with a maintenance of the LDL/HDL cholesterol ratio. Recent drug trials targeting HDL-cholesterol have been unsuccessful in reducing cardiovascular events, and thus it is unclear if raising HDL-cholesterol with chronic egg intake is beneficial. Other important changes with egg intake include potentially favorable effects on lipoprotein particle profiles and enhancing HDL function. Overall, the increased HDL-cholesterol commonly observed with dietary cholesterol feeding in humans appears to also coincide with improvements in other markers of HDL function. However, more investigation into the effects of dietary cholesterol on HDL functionality in humans is warranted. There are other factors found in eggs that may influence risk for heart disease by reducing serum lipids, such as phospholipids, and these may also modify the response to dietary cholesterol found in eggs. In this review, we discuss how eggs and dietary cholesterol affect serum cholesterol concentrations, as well as more advanced lipoprotein measures, such as lipoprotein particle profiles and HDL metabolism.